Volvulus U-Shaped transverse colonic duplication: Report of a case and literature review - Ruankha Bilommi (Journal of Pediatric Surgery Case Reports, 2017)
Tubular duplication of the colon is very rare especially in adulthood, because it is frequently symptomatic earlier in newborn life, so only few cases are reported in literature. Several theories are proposed to explain the onset and the evolution of gut malformations as the aberrant lumen recanalization or the diverticular theory, the alteration of the lateral closure of the embryonal disk or finally the dorsal protrusion of the yolk-sac for herniation or adhesion to the ectoderm for an abnormality of the longitudinal line, but none clarifies the exact genesis of duplication [1–3]. U Shaped transverse colonic duplication with volvulus has never been reported before and very rare in condition in gastrointestinal duplication.